Technology in Learning in Rural Utilization Areas as an Alternative for Educational Development: Case Study of KKN at SDN Rancakole - Malik, Miftahul; Dwiyanti, Ratna Alya; Azzahra, Nanda Nur; Agustiansyah, Rizky; Zidan, Muhammad; Maesaroh, Siti; Maulana, Reza Aditia; Fadhila, Dehya Nisrina; Nurhikmah, Ima; Sunarti, Pipit; Ichsan, Muhammad (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
Education is the main foundation for shaping quality and competitive human resources. However, there are disparities in access to and quality of education between urban and rural areas in Indonesia. This article discusses the implementation of Community Service Learning (KKN) conducted by students of the Islamic University of Nusantara at SDN 2 and SDN 3 Rancakole, Arjasari District, Bandung Regency, from August to September 2024. This activity aims to integrate technology into the learning process to address educational challenges in rural areas. Through a qualitative approach, this research evaluates the impact of technology application in learning as well as the challenges faced. The results indicate that the use of technology, such as projectors and digital learning media, can enhance student participation and motivation to learn. Additionally, training for teachers and students on the utilization of technology is also key to improving education quality. It is hoped that this innovation can serve as a model for educational development in remote areas.